2000
DOI: 10.1021/bi9926734
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Heparin with a Synthetic Pentadecapeptide from the C-Terminal Heparin-Binding Domain of Fibronectin

Abstract: The synthetic pentadecapeptide FN-C/H II (KNNQKSEPLIGRKKT-NH(2)) has the sequence of the carboxy-terminal heparin-binding domain of module III(14) of fibronectin. Interaction of FN-C/H II with bovine lung heparin has been studied by (1)H and (23)Na NMR spectroscopy and by heparin affinity chromatography. FN-C/H II binds to heparin from pD <2 up to pD approximately 10; at higher pD, the binding decreases as the lysine side-chain ammonium groups are titrated. Na(+) counterions are displaced from the counterion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Experimental values of 0.58 and 0.63 have been reported (46,47). Counterions are released when heparin binds to peptide, as described by the following binding equilibrium for sodium heparinate (38,43,48): (5) The number of Na + ions displaced by peptide, n, is equal to Zψ, where Z represents the number of ionic interactions the peptide makes with heparin and ψ is the apparent fraction of a Na + condensed per heparin anionic charge. ψ includes both the fraction of a Na + ion condensed per heparin anionic charge (θ) and the screening effect of condensed Na + ions on the interactions of residual heparin anionic charges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental values of 0.58 and 0.63 have been reported (46,47). Counterions are released when heparin binds to peptide, as described by the following binding equilibrium for sodium heparinate (38,43,48): (5) The number of Na + ions displaced by peptide, n, is equal to Zψ, where Z represents the number of ionic interactions the peptide makes with heparin and ψ is the apparent fraction of a Na + condensed per heparin anionic charge. ψ includes both the fraction of a Na + ion condensed per heparin anionic charge (θ) and the screening effect of condensed Na + ions on the interactions of residual heparin anionic charges.…”
Section: Discussionmentioning
confidence: 99%
“…If so, the apparent pK A s of the lysine ammonium groups that interact with heparin will be increased (38). pK A values can be determined for each lysine ammonium group in a peptide from the pH dependence of the chemical shifts of the side chain C ε H 2 protons (39).…”
Section: Effect Of Heparin On Titration Of the Lysine Ammonium Groupsmentioning
confidence: 99%
“…Na ϩ ) can interact with heparin by delocalized, long range electrostatic interactions and by direct binding to ionic sites. Displacement of counter-ions upon heparin binding to protein has been experimentally demonstrated (31). In cases where a plot of log K d obs against log [salt] is linear, the magnitude of the slope corresponds to the effective number of heparin counter-ions released upon its binding to a protein.…”
Section: Fig 2 Sds-page Analysis Of Wt and Variant Protein Cmentioning
confidence: 99%
“…This domain also supports cell adhesion and spreading through five peptides composed of basic residues that, in vitro, have been shown independently to bind heparin and/or chondroitin sulfate (33-36). Repeat III 14 contains three of the five basic peptides, one immediately N-terminal to the V region which may be inaccessible in the native molecule (37,38). X-ray crystallography studies by Sharma et al (16) confirmed the prediction that a cluster of six basic residues from one or more of these peptides come together to generate a positively charged "cradle" on one side of the molecule that forms the major heparin-binding site in III 13 .…”
Section: Discussionmentioning
confidence: 99%